The complete chloroplast genome of Eria lasiopetala (Willd.) Ormerod. Issue 12 (2nd December 2021) - Teng, Yun; Yang, Li; Zhang, Yan
Abstract: Eria lasiopetala (Willd.) Ormerod is an important ornamental plant and traditional Chinese medicine resource, but it is currently listed as a class II protected species due to its few resources in China. To further clarify the taxonomic status as well as provide genetic information for its conservation, the chloroplast genome of E. lasiopetala was assembled and characterized in this study. Results show that the genome is 158, 740 bp in length, including a large single copy, two inverted repeats, and a small single copy, their lengths are 88, 062, 26, 213, and 18, 252 bp, respectively. There are 132 genes in the chloroplast genome, among which the number of encoding protein genes, rRNA genes, and tRNA genes are 86, 8, and 38, respectively. The phylogenetic tree clearly shows that E. lasiopetala and Eria corneri cluster together with 100% support, rather than with Dendrobium group.